2018
DOI: 10.1177/1352458517737370
|View full text |Cite
|
Sign up to set email alerts
|

The aliens inside us: HERV-W endogenous retroviruses and multiple sclerosis

Abstract: Two human endogenous retroviruses of the HERV-W family are proposed as multiple sclerosis (MS) co-factors: MS-associated retrovirus (MSRV) and ERVWE1, whose env proteins showed several potentially neuropathogenic features, in vitro and in animal models. Phase II clinical trials against HERV-Wenv are ongoing. HERV-W/MSRV was repeatedly found in MS patients, in striking parallel with MS stages, active/remission phases, and therapy outcome. The HERV-Wenv protein is highly expressed in active MS plaques. Early MSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 35 publications
(121 reference statements)
1
47
0
Order By: Relevance
“…We focused on HERV-K because, of the dozens of HERV families, only HERV-W and HERV-K were repeatedly reported to have potentially pathogenic properties, both linked to the proteins coded by their env genes. The HERV-W is linked to multiple sclerosis [ 49 , 50 ], and the HERV-K to cancer [ 5 , 51 ] and amyotrophic lateral sclerosis [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…We focused on HERV-K because, of the dozens of HERV families, only HERV-W and HERV-K were repeatedly reported to have potentially pathogenic properties, both linked to the proteins coded by their env genes. The HERV-W is linked to multiple sclerosis [ 49 , 50 ], and the HERV-K to cancer [ 5 , 51 ] and amyotrophic lateral sclerosis [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yet there is mounting evidence that MS is tightly linked to EBV infection, whereby viral expression was observed in the CNS of MS cases 27 , 28 . It is also of importance to note that EBV is capable to express latent endogenous retroviral genes in the human genome, some of which are pro-inflammatory and have super-antigenic properties and have been shown to cause neurotoxic effects 29 . It is not possible to state whether EBV infection is the sole contributor or initiator of observed MS-based molecular changes in blood based on our analysis, but the literature suggests that multiple health-affecting causes are contributing factors to MS pathophysiology and/or initiation events, of which EBV is one of them.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble CD163 (sCD163) measured in serum has been examined as a biomarker in MS [79], while their study also confirmed the presence of human endogenous retrovirus (HERV-W) envelope epitopes on non-classical monocytes from patients with MS. It has previously been suggested that viral infections such as Epstein-Barr and subsequent activation of HERV-W, also known as the MS-associated retroviral element (MSRV), may be involved in the inflammatory demise of oligodendrocytes [80].…”
Section: Discussionmentioning
confidence: 99%